Real-Time Pressing Force System for Electrical Connectors on Printed Circuit Boards: doi: 10.14456/mijet.2019.2 - Khotabut, Ekkarat; Tonglim, Nattawut; Photong, Chonlatee (Engineering Access, 2019)
This paper presents a real-time pressing force display system for the connector pressing machine. The objectives of the research are to analyze the performance of the pressing machine and to ensure that the machine is ready to be used. Traditionally, most manufacturers assign the maintenance workers to measure pressing force using force gauge manually which may cause measurement errors and interrupt the operating processes. This research proposes an alternative system by using the pressure sensor (KEYANCE AP-C33W) to measure the pressure of the front camera connector pressing cylinder of the pressing machine, a microcontroller (Arduino UNO) to receive analogue signals from the pressure sensor and the load cell to measure the pressing force. After that, find the correlation equation of pressing force and analogue value with statistical analysis and then display by the real-time graph of pressing force using the C# program. The experimental results of the proposed system when implemented at the mobile phone manufacturing processes, Sony Technology (Thailand) Co., Ltd., indicated that the pressing force measured from the program has value closed to the pressing force measured by the proposed load cell, while providing the relatively low errors of front camera pressing cylinder, the microphone pressing cylinder and the keypad pressing cylinder of 0.001-0.03 %, 0.001-0.034%, and 0.001-0. 015 %, respectively.